2005
DOI: 10.1158/1078-0432.ccr-04-1469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Programmed Death-1 Ligand-1 and Programmed Death-1 Ligand-2 Expression in Human Esophageal Cancer

Abstract: Purpose:The negative regulatory programmed death-1/programmed death-1ligand (PD-1/PD-L) pathway inT-cell activation has been suggested to play an important role in tumor evasion from host immunity. In this study, we investigated the expression of PD-L1 and PD-L2 in human esophageal cancer to define their clinical significance in patients'prognosis after surgery. Experimental Design: PD-L1 and PD-L2 gene expression was evaluated in 41esophagectomy patients by real-time quantitative PCR. The protein expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
502
11
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 720 publications
(546 citation statements)
references
References 31 publications
26
502
11
7
Order By: Relevance
“…PD-L1 engagement of PD-1 may be one mechanism whereby tumors evade immunosurveillance by directly limiting effector T-cell activity. Several studies support the notion that PD-L1 expression and, in some cases, PD-L2 expression is associated with tumor aggressiveness and adverse patient outcome (14,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 77%
“…PD-L1 engagement of PD-1 may be one mechanism whereby tumors evade immunosurveillance by directly limiting effector T-cell activity. Several studies support the notion that PD-L1 expression and, in some cases, PD-L2 expression is associated with tumor aggressiveness and adverse patient outcome (14,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 77%
“…Some studies reported negative impact of PD-L1 and PD-L2 expression on patient survival in pancreatic cancer 31 and renal cell cancer 55 in addition to an inverse relationship with tumor infiltrating CD8 C lymphocytes in esophageal cancer. 43 However, others did not find a correlation with poor survival 32,33 and some showed an association with poor clinicopathological factors and increased immune cell infiltrate. 30 Thus, the prognostic relevance of PD-L1 and PD-L2 expression in tumors is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that PD-L1 is commonly upregulated on many different tumor types including melanoma [47], ovarian cancer [48], lung cancer [49], clear cell renal carcinoma [50], urothelial carcinoma [51], squamous cell carcinomas of the head and neck [52,53], esophageal cancer [54], cervical cancer [55], breast carcinoma [56], pancreatic cancer [57], gastric cancer [58], Wilms tumor [59] and glioblastoma [60], and that PD-1 is expressed in TILs, has created an important rationale for mAb blockade of this pathway for cancer immunotherapy.…”
Section: Pd-1/pd-l1 In Malignant Diseasesmentioning
confidence: 99%